YOUTUBE AS A SPEAKING TOOL: A CASE STUDY OF UNDERGRADUATE STUDENTS - Shumaila Aish Bahadur; Rai Hassan Iqbal; Dr Rai Zahoor Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of this study was to explore how YouTube videos can help students improve their speaking skills at the University level. This study also explored how YouTube videos can improve the accuracy, grammar and pronunciation of the students. Based on the study questions and goals, the research design was created, which was an experimental study. The participants of the study consisted of 15 undergraduate students both male and female. There were pre-test and post-test design groups along with treatment & intervention in it. Additionally, the study combined qualitative and quantitative methods to provide the data descriptively and numerically. The research findings were divided into two sections that covered the research process, covering the situation before the research and the implementation of the research. The results of this study suggested that watching YouTube in class can enhance the learning experience. Conclusion Based on the research findings showed that using YouTube videos can help students improve their speaking skills. The findings of the research confirmed the improvement in speaking skills. Fluency, vocabulary, grammar, and pronunciation all have seen gains in scores, as did other speaking-related categories. Based on the statements, it is concluded that YouTube videos improved student’s speaking skills during the learning process. This study also offered suggestions based on the justification and analysis for future research.